Is there clinical utility to replacement of an implantable loop recorder in patients who have previously undergone cryoballoon pulmonary vein isolation?. (19th May 2022) - Musat, D; Milstein, N; Saberito, M; Bhatt, A; Habibi, M; Preminger, M; Sichrovsky, T; Shaw, R; Mittal, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Implantable loop recorders (ILRs) are used for long-term ECG monitoring following catheter ablation in patients (pts) with atrial fibrillation (AF) to guide clinical management. However, little is known about what do when the ILR reaches end of service (EOS). Purpose: To identify pts who underwent replacement of their ILR and determine the diagnostic yield and clinical utility of the replacement device. Methods: We enrolled 222 consecutive pts with AF who underwent cryoballoon pulmonary vein isolation (CB PVI) and had an ILR. We identified pts who subsequently underwent ILR replacement. The diagnostic and clinical utility of the newly replaced ILR was determined. Results: The cohort included 56 pts (64 + 9 years; 35 [63%] male; 27 [48%] PAF; CHA2DS2-VASc 2.3 ± 1.5) in whom the initial ILR reached EOS. They were followed for 3.7 ± 2.1 years. Recurrent AF was observed in 41 (73%) of these pts; this triggered an intervention in 17 (41%) pts (Figure). Of the other 15 (27%) pts without any documented AF, anticoagulation was withheld in 13 [87%] pts. Following ILR replacement, 33 (80%) of the 41 pts had more AF (n=11 [33%] required an intervention) and 5 additional pts had AF for the first time. Conclusions: Our data show that after CB PVI, ILRs help guide decisions regarding rhythm management and oral anticoagulation. When the initial ILR was replaced by a second ILR, AF was detected (often for the first time) in some patients; the findings were used to guide clinical decision making in the entire cohort. Thus, at this time, it remains undefined when ECG monitoring of these pts can be stopped because it is no longer clinical meaningful.